KAREN’S DINER : THE ETHICAL OF BUSINESS ON CUSTOMER SATISFACTIONS - Agustin, Eka Nadya; Bahiroh, Eloh (Management Science Research Journal, 2023)
The success of a company depends on the satisfaction of customer. This research to determine the effect of business ethics on customer satisfactions. The sample data was been taken from 50 respondents of Karen’s Dinner Restaurant. The research method using statistic descriptive to explore the correlation between variable. The analysis regression used to search how much effect between independent and dependent variable. The result show that the business ethics have significant effect on customer satisfaction. The implication of the result is the business ethics and enhancing services excellent are required. A reputable company will always uphold corporate ethics and provide clients with high-quality service. It will have an impact on how satisfied customers are. Customers are most likely to conduct buying or make used product of a company, when a company have a high standards value and ethical business practices.